Betwixt and between: exploring the passage of liminal space - Key, Michelle (Rhodes University, Faculty of Humanities, Department of Fine Art, 2005)
The focus of this thesis is on the liminal space, limen being Latin for threshold. The liminal space is used as a means of figuring and reading artworks that appear to be in a process of becoming and disappearing. A dialectical and reciprocal reading is made of Bourgeois' "neo-Baroque" artwork Spider (1997) and Michelle Key's Betwixt-in-Between (2004). Liminality here is discussed within the theoretical framework of several key conceptual concerns, including abjection (as examined principally by Julia Kristeva), Baroque thought (as discussed by Mieke Bal, Gilles Deleuze, Jacques Lacan and Slavoj Å½iÅ¾ek) and allegory (as figured primarily by Walter Benjamin and commentators on Benjamin's writings). What links these concerns are their focus on indeterminacy, instability, and process as opposed to certitude and finitude. The exploration of the inscription of time in space; that is the temporal process, which gives rise to, which produces, the spatial dimension, is attempted in order to make meaning, however provisionally, of what may be argued to destabilise meaning and to consider possibilities for both art-making and interpretation that would engage critically with this instability.
Keywords: Bourgeois, Louis, 1911- -- Spider; Art and anthropology; Art criticism; Liminality